2007
DOI: 10.1002/sce.20203
|View full text |Cite
|
Sign up to set email alerts
|

Understanding engagement: Science demonstrations and emotional energy

Abstract: Although beloved of some chemists and physicists, science demonstrations have been criticized for stifling inquiry and assisting teachers to maintain a power differential between themselves and students in the classroom. This interpretive study reports the unexpected positive learning outcomes for urban science students in two chemistry classes that resulted from the use of science demonstrations during a unit on gas laws. Beginning with an examination of science demonstrations as sites of interactions, resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(53 citation statements)
references
References 28 publications
1
47
0
5
Order By: Relevance
“…As we have noted in other studies of preservice science teachers (Bellocchi et al 2014) in Australia and Bhutan (Rinchen, Ritchie and Bellocchi 2015) and as reported in studies with high school science students in the US by Olitsky (2007) and Milne and Otieno (2007), science demonstrations create a resource that focuses the attention of the class and produces shared emotions and emotional energy within the group. Similarly, we found the online students expressed excitement and enjoyment towards the demonstration in the present study even though they viewed the lecture video alone (i.e., without physical co-presence).…”
Section: Understandings and Implications For Social Bonds In Online Lsupporting
confidence: 61%
See 1 more Smart Citation
“…As we have noted in other studies of preservice science teachers (Bellocchi et al 2014) in Australia and Bhutan (Rinchen, Ritchie and Bellocchi 2015) and as reported in studies with high school science students in the US by Olitsky (2007) and Milne and Otieno (2007), science demonstrations create a resource that focuses the attention of the class and produces shared emotions and emotional energy within the group. Similarly, we found the online students expressed excitement and enjoyment towards the demonstration in the present study even though they viewed the lecture video alone (i.e., without physical co-presence).…”
Section: Understandings and Implications For Social Bonds In Online Lsupporting
confidence: 61%
“…Beneficial emotional outcomes such as improved engagement and willingness to adopt the chemistry symbols used in science class have been reported in studies seeking to connect emotions with learning science through demonstrations (Milne and Otieno 2007). Related research has also shown that students from disadvantaged backgrounds may be more inclined to participate in science through discussion about discrepant events, because these demonstrations provide a central focus of attention for the class and they elicit emotional reactions.…”
Section: Technology-mediated Learning and Emotionmentioning
confidence: 99%
“…In both cases, the picture is worth a thousand words. ‖ Milne and Otieno (2007) have found lecture demonstrations important in forging personal relationships between the instructor and students, particularly for -urban students belonging to marginalized groups‖, where the inclusion of lecture demonstrations produced greater student engagement during, and after, the introduction of concepts. Shakhashiri (2011b), too, promotes the use of demonstrations to enhance learning by strengthening interpersonal relationships:…”
Section: Justifications For Use Of Demonstrationsmentioning
confidence: 99%
“…The demonstration is an important pedagogical method in other practical subjects, including science (Milne and Otieno 2007) and physical education (Mosston and Ashworth 2002). In design and technology, it builds on the traditions of apprenticeship and craft education of ''demonstration, observation and constant practice'' (Mason and Houghton in Sayers et al 2002, p. 44).…”
Section: Introductionmentioning
confidence: 99%